ENZYME LINKED IMMUNOSORBENT ASSAY - Yakubova D.M; Isomadinova L.K; Miyliyeva M.H (TADQIQOTLAR.UZ, 2024)
Аnnotation: The current state of enzyme immunoassay of medicinal substances is considered. The main methods for obtaining and purifying specific antibodies, immunogens, enzyme conjugates are described. Examples of definitions are given medicinal substances by enzyme immunoassay, lists the possible causes of errors in the determination of medicinal substances by enzyme immunoassay methods analysis.